FAKTOR FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Rika Fitryani; citra ramayani; desi areva (STKIP PGRI Sumatera Barat, 2021)
This study aims to analyze: 1) the effect of profitability on firm value, 2) the effect of capital structure on firm value, 3) the effect of firm size on firm value, 4) the effect of sales growth on firm value, 5) the effect of the current ratio on firm value, 6) the influence of profitability, capital structure, company size, sales growth and current ratio together affect firm value. The results of this study indicate that: profitability has a significant effect on firm value, capital structure has no significant effect on firm value, firm size has a negative effect on firm value, sales growth has no significant effect on firm value, current ratio has a significant effect on firm value in sub-sector companies. food and beverages listed on the Indonesia Stock Exchange (BEI) 2013-2017